( √ 1 2 + 3 √ 1 5 − 4 √ 1 3 5 ) ⋅ √ 3
a,1/3 .(x-2/5)=3/4 b, 7/3:(x-2/3)=4/5 c,1/3.(x-2/5)=4/5 d, 2/3.(x-1/2)-1/4.(x-2/5)=7/3 e,3/7 .(x-2/3)+1/2=5/4.(x-2) f,1/2.(x-3)+1/3.(x-4)+1/4.(x-5)=1/5 g,[2/3.(x-1/2)-4/5]:(x-1/3)=21/5 h, {x-[1/2.(x-3)+11/5]}:(x-1/2)=3/5 i,x.(x-2/5)-(x+2).x+11/4=4/3
a: =>x-2/5=3/4:1/3=3/4*3=9/4
=>x=9/4+2/5=45/20+8/20=53/20
b: =>x-2/3=7/3:4/5=7/3*5/4=35/12
=>x=35/12+2/3=43/12
c: 1/3(x-2/5)=4/5
=>x-2/5=4/5*3=12/5
=>x=12/5+2/5=14/5
d: =>2/3x-1/3-1/4x+1/10=7/3
=>5/12x-7/30=7/3
=>5/12x=7/3+7/30=77/30
=>x=77/30:5/12=154/25
e: \(\Leftrightarrow x\cdot\dfrac{3}{7}-\dfrac{2}{7}+\dfrac{1}{2}-\dfrac{5}{4}x+\dfrac{5}{2}=0\)
=>\(x\cdot\dfrac{-23}{28}=\dfrac{2}{7}-3=\dfrac{-19}{7}\)
=>x=19/7:23/28=76/23
f: =>1/2x-3/2+1/3x-4/3+1/4x-5/4=1/5
=>13/12x=1/5+3/2+4/3+5/4=257/60
=>x=257/65
i: =>x^2-2/5x-x^2-2x+11/4=4/3
=>-12/5x=4/3-11/4=-17/12
=>x=17/12:12/5=85/144
bài 1:
1/4 + 2/3 2/7 + 2/3 2/5 + 1/3 2/3 + 1/2 1/3 + 3/5 4/5 + 1/3
1/8 + 3/4 1/36 + 5/12 1/3 + 1/6 + 1/18.
bài 2:
15/16 - 3/16 17/18 - 5/6 3/4 - 4/9 1/2 - 2/5 5/6 - 3/10 3-1/3
4/5 - 1/10 5/2 - 1 5/8 - 2/5.
1+1+1+1+1+1+1=?
2+2+2+2+2+2+2=?
3+3+3+3+3+3+3=?
4+4+4+4+4+4+4=?
5+5+5+5+5+5=?
Tính:
5 – 1 = … | 4 – 1 = … | 3 – 1 = … | 2 + 3 = …. |
5 – 2 = … | 4 – 2 = … | 3 – 2 = … | 3 + 2 = …. |
5 – 3 = …. | 4 – 3 = … | 2 – 1 = … | 5 – 2 = …. |
5 – 4 = …. | 5 – 3 = …. |
Lời giải chi tiết:
5 – 1 = 4 | 4 – 1 = 3 | 3 – 1 = 2 | 2 + 3 = 5 |
5 – 2 = 3 | 4 – 2 = 2 | 3 – 2 = 1 | 3 + 2 = 5 |
5 – 3 = 2 | 4 – 3 = 1 | 2 – 1 = 1 | 5 – 2 = 3 |
5 – 4 = 1 | 5 – 3 = 2 |
5-1=4 4-1=3 3-1=2 2+3=5
5-2=3 4-2=2 3-2=1 3+2=5
5-3=2 4-3=1 2-1=1 5-2=3
5-4=1 5-3=2
Tính:
5 – 1 = 4 | 4 – 1 = 3 | 3 – 1 = 2 | 2 + 3 = 5 |
5 – 2 = 3 | 4 – 2 = 2 | 3 – 2 = 1 | 3 + 2 = 5 |
5 – 3 = 2 | 4 – 3 = 1 | 2 – 1 = 1 | 5 – 2 = 3 |
5 – 4 = 1 | 5 – 3 = 2 |
Câu 15 A= 1/3-3/4+3/5+1/2007-1/36+1/25-2/9
Câu 16 A=1/3- 3/4- (-3/5)+ 1/64- 2/9- 1/36+ 1/15
Câu 17 A=1/2- 2/3+ 3/4- 4/5+ 5/6- 6/7- 5/6+ 4/5- 3/4+ 2/3- 1/2
15: A= 1/3-3/4+3/5+1/2007-1/36+1/15-2/9
Sửa đề:
A=-3/4-2/9-1/36+1/3+3/5+1/15+1/2007
=-27/36-8/36-1/36+5/15+9/15+1/15+1/2007
=-1+1+1/2007=1/2007
16:
\(A=\dfrac{1}{3}+\dfrac{3}{5}+\dfrac{1}{15}-\dfrac{3}{4}-\dfrac{2}{9}-\dfrac{1}{36}+\dfrac{1}{64}\)
\(=\dfrac{5+9+1}{15}+\dfrac{-27-8-1}{36}+\dfrac{1}{64}\)
=1/64
17:
=1/2-1/2+2/3-2/3+3/4-3/4+4/5-4/5+5/6-5/6-6/7
=-6/7
Bài 1
a, Tính P=1+1/2(1+2)+1/3(1+2+3)+1/4(1+2+3+4)+....+1/2012(1+2+3+...+2012)
b,Tìm x thỏa mãn 4^5+4^5+4^5+4^5/3^5+3^5+3^5.6^5+6^5+6^5+6^5+6^5+6^5/2^5+2^5=2^x
Kho..................wa.....................troi.....................thi......................lanh.................ret.......................ai........................tich..........................ung.....................ho........................minh.....................cho....................do....................lanh
Kho..................wa.....................troi.....................thi......................lanh.................ret.......................ai........................tich..........................ung.....................ho........................minh.....................cho....................do....................lanh
>, <, = ?
4…5 | 1…4 | 2…3 | 1…1 |
2…2 | 5…2 | 2…4 | 5…1 |
3…1 | 3…3 | 2…5 | 3…5 |
Lời giải chi tiết:
4 < 5 | 1 < 4 | 2 < 3 | 1 = 1 |
2 = 2 | 5 > 2 | 2 < 4 | 5 > 1 |
3 > 1 | 3 = 3 | 2 < 5 | 3 < 5 |
2/5+2/3+3/4
2/6+3/12
5/6+1/3
1/3+5/12+5/6
5/8+4/7
1/5+5/35
5/8+3/4
1/6+1/3+1/12
1/6+5/24+2/3
7/3+8/7
2/5+1/6
1/7+1/4+6/7+3/4
giúp với
và ai giải được gọi cụ
\(\dfrac{2}{5}+\dfrac{2}{3}+\dfrac{2}{4}\)
= \(\dfrac{24}{60}\) + \(\dfrac{40}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{64}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{47}{30}\)
\(\dfrac{2}{6}+\dfrac{3}{12}\)
= \(\dfrac{4}{12}\) + \(\dfrac{3}{12}\)
= \(\dfrac{7}{12}\)
\(\dfrac{5}{6}\) + \(\dfrac{1}{3}\)
= \(\dfrac{5}{6}\) + \(\dfrac{2}{6}\)
= \(\dfrac{7}{6}\)
9/10
17/36
7/6
19/12
67/56
12/35
11/8
7/12
25/24
73/21
17/30
2
ok chưa bạn!
\(\dfrac{1}{3}\) + \(\dfrac{5}{12}\) + \(\dfrac{5}{6}\)
= \(\dfrac{4}{12}\) + \(\dfrac{5}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{9}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{19}{12}\)
\(\dfrac{5}{8}\) + \(\dfrac{4}{7}\)
= \(\dfrac{35}{56}\) + \(\dfrac{32}{56}\)
= \(\dfrac{67}{56}\)
\(\dfrac{7}{3}\) + \(\dfrac{8}{7}\)
= \(\dfrac{49}{21}\) + \(\dfrac{24}{21}\)
= \(\dfrac{73}{21}\)
\(\dfrac{1}{5}+\dfrac{5}{35}\)
= \(\dfrac{7}{35}\) + \(\dfrac{5}{35}\)
= \(\dfrac{12}{35}\)
Tính:
5 - 1 = 1 + 4 = 2 + 3 =
5 - 2 = 4 + 1 = 3 + 2 =
5 - 3 = 5 - 1 = 5 - 2 =
5 - 4 = 5 - 4 = 5 - 3 =
5 - 1 = 4 1 + 4 = 5 2 + 3 = 5
5 - 2 = 3 4 + 1 = 5 3 + 2 = 5
5 - 3 = 2 5 - 1 = 4 5 - 2 = 3
5 - 4 = 1 5 - 4 = 1 5 - 3 = 2
5-1=4 1+4=5 2+3=5
5-2=3 4+1=4 3+2=5
5-3=2 5-1=4 5-2=3
5-4=1 5-4=1 5-3=2
1) (3x-2)/3-2=(4x+1)/4
2) (x-3)/4+(2x-1)/3=(2-x)/6
3) 1/2 (x+1)+1/4 (x+3)=3-1/3 (x+2)
4) (x+4)/5-x+4=x/3-(x-2)/2
5) (4-5x)/6=2(-x+1)/2
6) (-(x-3))/2-2=5(x+2)/4
7)2(2x+1)/5-(6+x)/3=(5-4x)/15
8) (7-3x)/2-(5+x)/5=1
9)(x-1)/2+3(x+1)/8=(11-5x)/3
10)(3+5x)/5-3=(9x-3)/4